Being In-between : Middle Income Groups in Uganda and Their Forms (and Absences) of Political and Social Mobilization - (:unkn) unknown (My University, 2018)
This thesis aims at a double deconstruction: of the applicability of the notion ofmiddle class in the African context and the hopes for it to be a motor of democratization,that are sometimes attached. Choosing a good, but average economicperformer like Uganda, allows us to examine the hype of “Africa rising” beyond thecontinent’s economic giants. Through a qualitative study of the lives, livelihoodsand life trajectories of Ugandans who would economically belong to the middleclass, according to the African Development Bank, we try to see whether we cansingle out specific middle class characteristics, that would allow us to better understandthis stratum and determine whether we can speak of a class or mere incomegroups. We then proceed to analyze their political attitudes, voting behavior,participation and their point of view on protest in Uganda. Finding that they arerather critical of the current regime, but abstaining from political participation, weeventually turn to their leisure activities – an important vector that can feed intosocial mobilization once it takes place – to analyze the values negotiated, the attitudesexpressed and the preferences manifested, in order to find any evidencethat will suggest that these groups will contribute positively to democratization,due to their middle class status.
Keywords: African Research